Application of health behavior theories to breast cancer screening among Asian women - Ahmadian, Maryam; Abu Samah, Asnarulkhadi (Asian Pacific Organization for Cancer Prevention, 2013)
Background: Although breast cancer is a major public health worry among Asian women, adherence to screening for the disease remains an obstacle to its prevention. A variety of psycho-social and cultural factors predispose women to delay or avoidance of screening for breast cancer symptoms at the early stages when cure is most likely to be successful. Yet few interventions implemented to date to address this condition in this region have drawn on health behavior theory. Materials and Methods: This paper reviews the existing literature on several cognitive theories and models associated with breast cancer screening, with an emphasis on the work that has been done in relation to Asian women. To conduct this review, a number of electronic databases were searched with context-appropriate inclusion criteria. Results: Little empirical work was found that specifically addressed the applicability of health theories in promoting adherence to the current breast cancer prevention programs Among Asian women. However, a few studies were found that addressed individual cognitive factors that are likely to encourage women’s motivation to protect themselves against breast cancer in this region of the world. The findings suggest that multi-level, socio-cultural interventions that focus on cognitive factors have much promise with this issue. Conclusions: Interventions are needed that effectively and efficiently target the personal motivation of at-risk Asian women to seek out and engage in breast cancer prevention. Concerning implications, personal motivation to seek out and engage in individual preventive actions for breast cancer prevention among Asian women is a timely, high priority target with practical implications for community development and health promotion. Further studies using qualitative, anthropologic approaches shaped for implementation in multi-ethnic Asian settings are needed to inform and guide these interventions.